The Role of Madrasah Heads’ Academic Supervision in Enhancing Teachers’ Creativity - Riska Nur Aulia; Alimulloh Alimulloh (At Tadbir: Journal of Islamic Education Management is published by the Islamic Education Management Study Programme, IAI al Urwatul Wutsqo, Jombang, East Java, Indonesia., 2026)
Academic supervision in madrasahs is often perceived as an administrative task and therefore does not yet fully encourage teachers’ creativity. This study aims to analyse the implementation of academic supervision by madrasah heads in enhancing teachers’ creativity, as well as to identify the factors that support and hinder this process. The research employs a qualitative approach using a case study design.The data were collected through interviews, observation and documentation, and were subsequently analysed using the Miles and Huberman interactive model, employing triangulation techniques.The research findings indicate that the implementation of academic supervision takes place through three main stages: participatory planning, a humanistic approach to implementation, and reflective evaluation. Planning is carried out through open dialogue to build teachers’ psychological readiness. During implementation, the headteacher acts as a discussion partner who encourages teachers to experiment with innovative teaching methods and resources. The evaluation was conducted in a collaborative manner, focusing on practical solutions and sustainable capacity-building. Enabling factors included supportive leadership, the availability of technological facilities, and a collaborative culture, whilst the main barriers were time constraints and the digital literacy gap. This study proposes a collaborative, participatory-humanistic model of academic supervision as an implementation framework that emphasises dialogue, mentoring and ongoing reflection to systematically and contextually enhance teachers’ creativity within the madrasah environment.